Application of Problem-Based Learning Models to Improve Ability to Understand Geometry Materials in SD Muhammadiyah 11 Surabaya - Rahmawati, Irma Dwi; Afiani, Kunti Dian Ayu; Faradita, Meirza Nanda (Widyagogik, 2023)
One of the successes of student learning is influenced by the quality or ability of the teacher in managing the learning process. This study aims to (1) describe the application of the problem based learning model to improve student learning outcomes in geometry material (2) to determine the increase in student learning outcomes using the problem based learning model. This research is a class action research (CAR). The research subjects were 3rd grade students of Adh Dhuha SD Muhammadiyah 11 Surabaya. The results of this study are (1). The research was conducted in two cycles, where each cycle had four stages, namely planning, implementing, observing and reflecting. (2). The increase in learning outcomes starting from the pre-cycle was 68.62, cycle 1 was 83.1, cycle 2 was 94.14 and the percentage of classical completeness in the pre-cycle was 65.51%, cycle 1 was 79.31% then experienced an increase of 13, 79% cycle 2 to 93.10% included in the good category. The development of student learning outcomes in affective and cognitive aspects has also increased. The affective aspect of students increased by 11.37% from cycle I of 68.97% to 80.34% in cycle II. While the psychomotor aspects of students experienced an increase of 18.11%, namely from cycle I of 72.84% to 90.95% in cycle II. Student learning outcomes in all aspects have achieved success. From the research results obtained, it was concluded that the problem based learning model could improve the learning outcomes of 3rd graders of Adh Dhuha SD Muhammadiyah 11 Surabaya. This research can be used by elementary school teachers as a reference to improve grade 3 student learning outcomes in geometry material.